2010
DOI: 10.1111/j.1365-2893.2009.01159.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis D outbreak among children in a hepatitis B hyper-endemic settlement in Greenland

Abstract: Hepatitis B virus (HBV) infection is endemic in Greenland with 5-10% of the population being HBsAg-positive (chronic carriers). Surprisingly, despite of the high prevalence of HBV infection, acute and chronic hepatitis B, liver cirrhosis and primary hepatocellular carcinoma appear much less frequently than expected. The reasons for the low frequencies are unknown, but as a consequence implementation of a childhood HBV vaccination programme, though debated for years, has never been instituted. We describe an ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 28 publications
0
20
2
Order By: Relevance
“…This was further confirmed in direct comparisons of the frequencies of HBsAg, anti-HBs, and anti-HBc. The lower HBsAg frequency in West Greenland compared with previous findings (7%) by Langer [15] and (19%) by Børresen [20] may likely be due to differences in recruitment of participants. in one settlement on the west coast [20] and 29% in Ammassalik district in East Greenland [8] as discussed [8].…”
Section: Discussioncontrasting
confidence: 55%
“…This was further confirmed in direct comparisons of the frequencies of HBsAg, anti-HBs, and anti-HBc. The lower HBsAg frequency in West Greenland compared with previous findings (7%) by Langer [15] and (19%) by Børresen [20] may likely be due to differences in recruitment of participants. in one settlement on the west coast [20] and 29% in Ammassalik district in East Greenland [8] as discussed [8].…”
Section: Discussioncontrasting
confidence: 55%
“…Very recently, it has been reported that Greenland is still endemic for chronic HBV with a prevalence of 5-10% in 2011 [72]. However, even with a high endemic rate of HBV infection, incidence of HCC and cirrhosis were not substantially different from Denmark [73][74], which is not considered endemic due to an HBsAg prevalence of 0.1% [75]. Genotype D and B5 are predominant in Greenland, and a high incidence of B5 infection may explain the relatively low occurrence of HCC and cirrhosis [76][77].…”
Section: Hbv Epidemiologymentioning
confidence: 99%
“…HDV continues to be an important health issue in the Brazilian Amazon despite the implementation of HBV vaccination in rural areas; in blood collected from HBsAg carriers along the banks of the Purus River in 2005 -2006, the prevalence of anti-HD was 41.9% (Braga et al 2012). Outbreaks of severe and fulminant hepatitis developing on a background of high-HBV endemicity have been reported in the last 20 years, also from Russia (Flodgren et al 2000), Greenland (Børresen et al 2010), and Mongolia (Tsatsralt-Od et al 2006).…”
Section: Epidemiology Of Hdv At the Fingertips In The 1980s -1990smentioning
confidence: 99%